ANALISIS STRATEGI SOCIAL MEDIA MARKETING DI INSTAGRAM RAJA PARFUM - Malvin Agustino,; Yulia Herman,; Rezky Dwiham Ginting,; Anggun Dea Ananda,; Annisya Mega Dwi Handayani,; Antony Sentoso, (Jurnal Cakrawala Ilmiah, 2023)
In the advanced digital era, social media marketing strategies have become the key to promoting brands and products on Instagram. Raja Parfum needs to develop an effective marketing strategy by understanding the target market and characteristics of Instagram users. Appealing visual content can enhance brand attractiveness, while understanding Instagram's algorithms and features helps maximize marketing potential. User interaction and engagement are important for building strong relationships, and performance analysis aids in evaluating strategies. Raja Parfum's Instagram account needs to enrich content variety and actively interact to enhance follower engagement and brand presence.